RELASI GENDER PEREMPUAN KARIR DALAM KELUARGA : STUDI PADA DOSEN PEREMPUAN IAI AL-KHOZINY BUDURAN SIDOARJO - Zona Rahma Daniar; Ratna Suraiya (Journal of Islamic Shariah and Research Applications, 2026)
Gender relations are a power relationship between men and women that can be seen in the scope of ideas, practices and representations that include the division of labor, roles, and allocation of resources between men and women. In a family, gender relations are based on attitudes of mutual understanding, mutual recognition, mutual responsibility and cooperation, as well as loyalty and sincerity of love for the sake of family harmony. This study aims to determine gender relations in the families of female lecturers at IAI Al-Khoziny, so that it can be known whether gender relations are achieved or not. The method used by the author is a qualitative descriptive method using interview and documentation methods as data collection tools. Interviews were conducted with female lecturers at IAI Al-Khoziny, while documentation was obtained from data related to the discussion. Based on the results of the study, it was concluded that in the families of female lecturers at IAI Al-Khoziny, gender relations were observed. Gender relations in the families of female lecturers at IAI Al-Khoziny are reflected in the existence of sharing roles in their daily lives, giving permission for their wives to participate as lecturers, understanding differences of opinion in terms of choosing roles in the household, and building good communication in the family. This shows that there are gender relations in the family of career women.